Katekese Kaum Muda di Ruang Media Sosial yang Dinamis - Venidora Palbeno; Monica Innanda Chiaralazzo; Intansakti Pius X (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Young people today live in a digital culture that makes social media the main space for communicating, forming identities, and finding meaning in life. In such situations, catechesis needs to adjust itself to remain relevant and able to reach them effectively. The use of social media opens up opportunities for the Church to present catechesis that is more interactive, visual, and contextual through various forms such as short videos, infographics, live broadcasts, and online discussions. A qualitative approach through literary studies and indirect observation shows that social media can increase the involvement of young people in faith formation because it is flexible and easily accessible. However, the use of social media also presents pastoral challenges, such as the potential for superficiality of content and a lack of deep appreciation of faith. Therefore, critical assistance and integration between digital catechesis and real community life are needed so that the faith of young people is sustained and strengthened in the life of the Church.